Mechanical prophylaxis to prevent venous thromboembolism on stroke patient: a Literature Review - Erna Fitriani; I Made Kariasa (Universitas Muhammadiyah Semarang, 2023)
Prevention of Venous Thromboembolism (VTE) is important in the treatment of stroke, including pharmacological and mechanical thromboprophylaxis. One of the post-stroke complications is Deep vein thrombosis (DVT), DVT can lead to pulmonary embolism (PE), and Venous thromboembolism (VTE) is manifested as DVT and PE. Stroke patients are at increased risk of developing DVT. This review aims to assess the clinical efficacy of mechanical prophylaxis for preventing venous thromboembolism in stroke patients. The articles were searched through PubMed, ScienceDirect, Sage Journals and ProQuest database. Keywords: